Peroxynitrite Activated Drug Conjugate Systems Based on a Coumarin Scaffold Toward the Application of Theranostics - Odyniec, Maria L.; Han, Hai-Hao; Gardiner, Jordan E.; Sedgwick, Adam C.; He, Xiao-Peng; Bull, Steven D.; James, Tony D. (Frontiers in Chemistry, 2019)
Two novel drug-conjugates based on a ‘coumarin linker’ have been designed for the synergic release of a therapeutic agent and fluorescent probe for the potential application of theranostics. The drug conjugates; CC-RNS and CI-RNS were designed to be activated by reactive oxygen species or reactive nitrogen species (ROS/RNS). The fluorescence OFF-ON response was triggered by the peroxynitrite-mediated transformation of a boronic acid pinacol ester to a phenol moiety with simultaneous release of the therapeutic agents (Confirmed by HRMS). The limit of detection for peroxynitrite using CC-RNS and CI-RNS was 0.29 µM and 37.2 µM, respectively. Both CC-RNS and CI-RNS demonstrated the ability to visualize peroxynitrite production thus demonstrating the effectiveness of these probes for use as tools to monitor peroxynitrite-mediated drug release in cancer cell lines.